Decision Making towards Maternal Health Services in Central Java, Indonesia - Sujana, Treesia; Barnes, Margareth; Rowe, Jennifer; Reed, Rachel (Department of Nursing, Faculty of Medicine, Diponegoro University, 2016)
Background: Indonesia has always been struggling with maternal health issue even after the Millennium Development Goals (MDGs) programs were done. Prior research findings identified many factors which influenced maternal health status in developing countries such Indonesia and even though various efforts had been made, the impact of the transformation of maternal health behavior was minimal.Purpose: This study aimed to seek an understanding of the factors influencing decisions towards maternal health services.Methods: A case study with a single case embedded design was employed. Interviews and Focus Group Discussions (FGDs) were held to collect data from 3 health workers and 40 maternal women in a sub-district in Central Java, Indonesia.Results: Interviews with the village midwives as the main health providers in the Getasan sub-district concluded that there were several factors influencing the women's decisions towards maternal services. The factors were options to have services with other health workers outside the area, and shaman services as alternative care and family influencing maternal health behaviors. The analysis of the FGDs also supported the village midwives’ statements that in spite of their awareness towards the available maternal health services, the existence of shamans and traditional beliefs strongly affected their decision.Conclusion: The findings in this study showed that cultural issues prevented the maximum maternal health status in Getasan sub-district. This study recommends Puskesmas (Primary Health Care) as the first level of health institutions in Indonesia to support the village midwives’ roles within their target area.